Synthesis of Phosphinoboranes via Coordination-Induced Bromine Abstraction of an Isolable Phosphinyl Radical with Bromoboranes - Ishida, Shintaro; Katayama, Yasuhiro; Hirakawa, Fumiya; Iwamoto, Takeaki (Synthesis, 2024)
A stable dialkylphosphinyl radical reacted with bromoboranes to afford the corresponding phosphinoboranes accompanied with a bromophosphine under neutral condition at room temperature. The obtained phosphinoboranes have almost planar structures and have an effective P–B dative π-bond. The formation of phosphinoboranes would proceed via coordination-induced bromine abstraction from bromoboranes as a pivotal step, which was supported by the computational study.
Keywords: phosphine; borane; radical; halogen abstraction; bond dissociation energy; dative bond; computational study